1961
DOI: 10.1042/bj0810514
|View full text |Cite
|
Sign up to set email alerts
|

Studies on protein and nucleic acid metabolism in virus-infected mammalian cells. 4. The localization of metabolic changes within subcellular fractions of Krebs II mouse-ascites-tumour cells infected with encephalomyocarditis virus

Abstract: Martin, Malec, Sved & Work (1961 b) showed that, during a single growth cycle, infection with encephalomyocarditis virus caused no changes in the total deoxyribonucleic acid, ribonucleic acid or protein of the host ascites-tumour cell. However, by the use of [6-14C]orotic acid and [14C]valine, it was shown that there were substantial changes in the rates of turnover of ribonucleic acid and protein at different times during the cycle of virus growth. In particular, about 5 hr. after infection there was a strik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1962
1962
1982
1982

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…A report (29) which states that the polymerase from HeLa cells infected with poliovirus is associated with the nuclear fraction is difficult to interpret, since the cells were fractionated after storage at -20 C. Recent data (23, 24) on the distribution of viraldirected synthesis of RNA by Krebs ascites cells inlfected with EMC virus also indicate that it occurs in the cytoplasm. Earlier findings (15,58) which implicated the nucleus as the site of synthesis of viral RNA probably resulted from undetected cytoplasmic contamination of the nuclei (16,23).…”
Section: Intracellular Location Of Viral-directedmentioning
confidence: 98%
See 1 more Smart Citation
“…A report (29) which states that the polymerase from HeLa cells infected with poliovirus is associated with the nuclear fraction is difficult to interpret, since the cells were fractionated after storage at -20 C. Recent data (23, 24) on the distribution of viraldirected synthesis of RNA by Krebs ascites cells inlfected with EMC virus also indicate that it occurs in the cytoplasm. Earlier findings (15,58) which implicated the nucleus as the site of synthesis of viral RNA probably resulted from undetected cytoplasmic contamination of the nuclei (16,23).…”
Section: Intracellular Location Of Viral-directedmentioning
confidence: 98%
“…Subsequent studies in which the synthesis of macromolecules was determined by measuring the rate of incorporation of labeled precursors by infected cells confirmed this conclusion. The results of these studies showed that the rate of synthesis of RNA and protein by many strains of mammalian cells is depressed soon after infection with polio- (45,85), mengo- (8,10,31,66), Me (39,75), or EMC virus (58). Inhibition of DNA synthesis, on the other hand, occurs only toward the end of the replicative cycle and, therefore, appears to represent a secondary host response.…”
Section: Introductionmentioning
confidence: 99%
“…It has been well known since the early 1960s that picornaviruses inducean inhibition of host cell transcription [3,21,22] and that virusspecific protein synthesis appears to be respon sible for RNA synthesis shut-off [8]. Since it has been found that cytoplasmic extracts of poliovirus-infected cells can inhibit transcrip tion in uninfected, isolated nuclei [10b], the next step was to see if poliovirus proteins could be demonstrated within the host cell nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the small ribonucleic acid RNA viruses, it appears that the cell nucleus plays little or no direct role in viral replication. However, for a wide variety of viral agents such as tobacco mosaic virus (11,19), encephalomyocarditis virus (3,7,16), and influenza virus (13), the possibility that the nucleus has an important function in RNA replication has been suggested.…”
mentioning
confidence: 99%